Micro Drilling 3D Printed Cobalt Chromium Molybdenum for Biomedical Applications : An Experimental Study on the Tool Wear and Machinability - Mohd Affifudin, Abdul Patar; Mohd Azlan, Suhaimi; Safian, Sharif; Amrifan S., Mohruni; Zhuang, Kejia (Springer Nature, 2025)
This paper presents the evaluation and observation of the drillability characteristics of cobalt chromium molybdenum (CoCrMo) produced through 3 dimensional (3D) Additive Manufacturing technologies named Selective Laser Sintering. CoCrMo is regarded as one of the advanced materials which are currently garnering popularity in both engineering and medical applications. However, this material falls under the hard-to-cut materials category due to its unique properties such as high strength, toughness, wear resistance as well as low thermal conductivity. All these tend to hinder the machinability resulting in rapid tool wear and subsequently shorter tool life. 2 mm diameter holes were drilled on a 5-axis high precision machine under flood cutting conditions with varying cutting speed and tool geometry (point angles). Drilling was conducted on a 3D printed CoCrMo (60 × 60 × 4) plate, forces and tool wears are the outputs recorded from the experiments conducted. The best combination of tool geometry and cutting speed on machining 3D CoCrMo are then identified. The best combination when micro drilling 3D printed CoCrMo is with 50 m/min and using tool B (130° point angle) drill bit. This combination generated the least thrust force and the lowest tool wear overall, 208.995 N and 0.089 mm wear respectively. The result from this study contributes to the minimization of tool wear and improvements in micro drilling efficiency by selecting appropriate machining parameters when working with CoCrMo alloys.